Analysis and Detection of Thumbprint Creases within 3 Generations of a Family in the Population of Himachal Pradesh - Priyanka Verma (International Journal of Medical Toxicology and Legal Medicine, 2024)
Fingerprints are the unique features that provide individuality. As one of the biometric traits, fingerprints are the most reliable and accurate method. They are considered one of the most significant types of evidence in court of law. Since ridges and valleys form fingerprint pattern, sometimes secondary creases or white lines break the pattern which are adjacent to epidermal ridges. Creases appear as straight, curved and jagged white lines which also act as a parameter for fingerprint identification purpose. However, the identification of these fingerprint impressions can be altered by various factors such as dryness, injuries, deformities, dirt etc., by which the results may be altered or the significant rate of identification would decrease. In order to improve the performance of detection, this study is aimed to detect creases in thumbprints and to determine any genetic inheritance among three generations within the family. The study is done by taking samples from 15 families of Himachal Pradesh geographical region, which include grandfather, grandmother, father, mother and their child or children. It has been examined that there might be a link between the genetic inheritance of fingerprint creases within three generations of a family as 53.3% families showed inheritance from 1st to 3rd generation. And secondly, the average crease count in females have higher on left thumb (1.86) and males on right thumb (2) within the geographical region of Himachal Pradesh. It has been observed that the right thumb creases are slightly higher as compared to left in the population of Himachal Pradesh.